Virtual meetings experience in sports management organizations during the COVID-19 pandemic: A phenomenological inquiry - Sid Terason; Jing Yang; Anuchit Kulwanich (Cogent Business & Management, 2022)
This study seeks to understand how virtual meetings disrupt or propel the functioning of sports management organizations in Thailand during the COVID-19 pandemic, what is critical to executives meetings held during the time, and the impact on meeting attendees amid the public health crisis. A phenomenological approach was applied to this qualitative enquiry. We conducted a study on a group of the executives in various sports entities in the country to achieve an understanding of their virtual meeting experiences. We gleaned new insights about this phenomenon through the experiences narrated by these individuals. The in-depth interview data were collected from nine executives selected using a purposeful sampling method. The codes relative to their virtual meetings experience were analyzed thematically on the basis of the media compensation theory. Six categories (resource use, communication, logistics, social etiquette, well-being, and interpersonal rapport) were grouped into three themes (organizational function, meeting operation, and personal impact). Future studies could incorporate other dimensions of virtual communication in these settings.
Keywords: 650; COVID-19; sports management organization; virtual meeting